MEDIA RICHNESS THEORY IN THE USE OF @Youngontop INSTAGRAM ACCOUNT AS AN INFORMATION MEDIUM FOR YOUNGER GENERATION - Dwi P., Declan Theofilus; Fitriani, Reni (Universitas Gunadarma, 2024)
This research aims to determine @youngontop's communication strategy in informing activities that are beneficial for the self-development and creativity of the younger generation. The theory used in this research is media richness theory. The method used is descriptive qualitative with data collection through observation, in-depth interviews, literature study and documentation. The paradigm in this research is constructivism. The results of this research are that the Instagram account @youngontop maximizes the features on Instagram in conveying information to the younger generation. Information about activities that the younger generation can take part in is conveyed creatively with photo illustrations, videos and also the use of language that is relevant to the younger generation. The choice of language is also very adapted to the trends of the younger generation in the hope that it will be interesting in conveying information about activities. The Instagram account @youngontop also has a message personalization strategy in the form of research to find out the preferences and needs of followers.